Updating the larval habitats of Aedes aegypti (Diptera: Culicidae) in Camagüey, Cuba - Diéguez, Lorenzo; Pino, Rafael; Andrés, Julio; Hernández, Arturo; Alarcón-Elbal, Pedro Mª; San Martín, José L. (Revista de Biología Tropical, 2016)
Several illnesses of vectorial origin have a great medical and veterinary relevance, due to the adaptations developed by the species involved in their transmission. To support preventive programs with updated ecological information of Ae. aegypti populations, an entomological survey was carried out in three Health Areas of Camagüey, Cuba, during low and high rain seasons of 2013. For this, we assessed the type and number of positive containers, quantified larvae and pupae in positive containers, according to the container location in or outside the house. Both the container representativeness percentage and the pupal index by specific containers were calculated (PIsC). The total of houses as well as the positive habitual-use and non-disposable containers were compared among weather seasons, using the non parametric Chi2 test. The existent relationship between the total of positive houses and the habitual-use and non-disposable container was explored through the test of proportions hypothesis, with a level of significance of P ≤ 0.05. Ae. aegypti colonized 73 different types of containers, being habitual-use and non-disposable a 23.2 %. This number included 76 % of the positive containers. The greatest larvae collections were obtained in exterior water tanks and barrels, with important pupal production (PIsC = 3.04 and 1.75, respectively), and as well as significant differences towards the rainy season respect to positive houses (PUIA: Chi2 = 32.89; P = 0.00; PUE: Chi2 = 127.44; P = 0.00 and PUJAM: Chi2 = 127.44; P = 0.00), and the habitual-use and non-disposable container (PUIA: Chi2 = 30.37; P = 0.00; PUE: Chi2 = 37.26; P = 0.00 and PUJAM: Chi2 = 81.82; P = 0.00). These data reinforce the priority given to the control and surveillance actions conducted by the community in their respective houses.